2009
DOI: 10.1053/j.gastro.2008.09.066
|View full text |Cite
|
Sign up to set email alerts
|

Liver Cell–Derived Microparticles Activate Hedgehog Signaling and Alter Gene Expression in Hepatic Endothelial Cells

Abstract: Background & Aims Angiogenesis contributes to vascular remodeling during cirrhosis. In cirrhotic livers, cholangiocytes and myofibroblastic hepatic stellate cells (MF-HSC) produce Hedgehog (Hh) ligands. During embryogenesis Hh ligands are released from ligand-producing cells in microparticles and activate Hh signaling in endothelial cells. We studied whether adult liver cell-derived microparticles contain Hh ligands that alter hepatic sinusoidal endothelial cells (SEC). Methods MF-HSCs and cholangiocytes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
177
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(183 citation statements)
references
References 33 publications
5
177
0
1
Order By: Relevance
“…PDGF-treated HSC and cholangiocytes release exosomes with hedgehog ligands, which induce hedgehog-dependent changes in SEC with upregulation of several genes leading to an angiogenic phenotype. Of note, bile duct ligation in mice increased the release of such exosomes, too, supporting further evidence for a key role of extracellular vesicles in liver fibrogenesis [76]. While HSC communicate with SEC via exosomes, the same seems to be true vice versa.…”
Section: Exosome Signaling As a New Form Of Sec/hsc Crosstalkmentioning
confidence: 60%
See 1 more Smart Citation
“…PDGF-treated HSC and cholangiocytes release exosomes with hedgehog ligands, which induce hedgehog-dependent changes in SEC with upregulation of several genes leading to an angiogenic phenotype. Of note, bile duct ligation in mice increased the release of such exosomes, too, supporting further evidence for a key role of extracellular vesicles in liver fibrogenesis [76]. While HSC communicate with SEC via exosomes, the same seems to be true vice versa.…”
Section: Exosome Signaling As a New Form Of Sec/hsc Crosstalkmentioning
confidence: 60%
“…Hedgehog ligands are known to activate downstream pathways in endothelial cells through exosomes during embryogenesis [75]. In a recent study, Witek et al [76] showed that those hedgehog ligands play an important role in HSC-SEC crosstalk and angiogenesis via exosomeenriched microparticles. PDGF-treated HSC and cholangiocytes release exosomes with hedgehog ligands, which induce hedgehog-dependent changes in SEC with upregulation of several genes leading to an angiogenic phenotype.…”
Section: Exosome Signaling As a New Form Of Sec/hsc Crosstalkmentioning
confidence: 99%
“…In vitro studies indicate that exosomes may up-regulate the expression of fibrolytic matrix metalloproteinase genes in HSCs (42,43). In other studies, exosomes were capable of transducing Hedgehog signals (13). Microparticles have also been implicated in cirrhosis and portal hypertension, with evidence that such particles may contain the angiogenic molecule VEGF and other studies providing evidence that these particles can mediate hemodynamic disturbances associated with cirrhosis (50).…”
Section: Discussionmentioning
confidence: 99%
“…CD63 and CD81) (9 -12). Recent studies have explored potential roles for exosomes in the pathogenesis of liver inflammation, fibrosis, and portal hypertension (13). An increase in this extracellular vesicle subtype has been postulated in patients with cirrhosis (14).…”
mentioning
confidence: 99%
“…Several lines of historical evidence support the concept that EMT is the biological bridge that links cirrhosis and HCC. First, markers of EMT have been detected in the blood of rodents and humans with cirrhosis (28,29). Second, various events that enhance the efficiency of cancer cell EMT predict cancer invasion, metastasis, and reduced survival in HCC patients.…”
Section: Cirrhosis Emt and Hccmentioning
confidence: 99%